COGNITIVE BIASES UNVEILED : FRAMING, TIME PRESSURE, AND CULTURAL UNCERTAINLY AVOIDANCE RESHAPE INVESTMENT DECISIONS THROUGH - Fauzananda Musrady, Raihan Aqil; Suzan, Leny; Mulia, Teodora Winda (PT. Media Edutama Nusantara, 2025)
This study aims to analyze the influence of framing, time pressure, and uncertainty avoidance on investment evaluation decision-making. This study uses an experimental approach based on fuzzy-trace theory and prospect theory rooted in behavioral finance. The experiment was conducted on final-year accounting students as a proxy for financial decision-makers, using a 2x2x2 factorial design to examine the influence of each variable. The analysis results indicate that information framing significantly influences investment decisions; participants who received information with negative framing tended to be more willing to take risks compared to those with positive framing. Time pressure was also found to affect decision accuracy, while uncertainty avoidance revealed significant differences in risk preferences. These findings reinforce evidence that psychological aspects and situational context play a significant role in financial decision-making, particularly in the evaluation of fixed asset investments. The practical implications of this study highlight the importance of developing information strategies and managerial controls in the long-term investment decision-making process.